2022
DOI: 10.1038/s41598-021-04095-w
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided fine-needle biopsy as a tool for studying the intra-tumoral microbiome in pancreatic ductal adenocarcinoma: a pilot study

Abstract: A new approach by investigating the intra-tumoral microbiome raised great interest because they may influence the host immune response and natural history of the disease. However, previous studies on the intra-tumoral microbiome of pancreatic ductal adenocarcinoma (PDAC) were mostly based on examining the formalin-fixed paraffin-embedded tumor specimens. This study aims to investigate the feasibility of using endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) as a complementary procedure of surgical bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The intrapancreatic microbiota of PC patients, analyzed by Pushalkar and colleagues, revealed a higher presence of Proteobacteria (45%) and Bacteroides (31%), with an increased bacterial abundance compared to healthy controls [5]. A higher concentration of Proteobacteria in the samples from the PC patients was found in a study of 187 patients and in a survey conducted on 1526 samples from different tumor types [46][47][48]. On the other hand, a study conducted by Geller et al suggested an enhanced ability to metabolize chemotherapies due to a higher abundance of Gammaproteobacteria [27,34].…”
Section: Intrapancreatic Microbiota In Pcmentioning
confidence: 94%
“…The intrapancreatic microbiota of PC patients, analyzed by Pushalkar and colleagues, revealed a higher presence of Proteobacteria (45%) and Bacteroides (31%), with an increased bacterial abundance compared to healthy controls [5]. A higher concentration of Proteobacteria in the samples from the PC patients was found in a study of 187 patients and in a survey conducted on 1526 samples from different tumor types [46][47][48]. On the other hand, a study conducted by Geller et al suggested an enhanced ability to metabolize chemotherapies due to a higher abundance of Gammaproteobacteria [27,34].…”
Section: Intrapancreatic Microbiota In Pcmentioning
confidence: 94%
“…A study compared the microbiome of pancreatic duct adenocarcinoma samples obtained using endoscopic ultrasound-guided fine-needle aspiration biopsy with those obtained by surgical resection, and the results showed that microorganisms obtained by biopsy were contained within surgically removed samples. 252 The organisms obtained from non-small cell lung cancer broncho alveolar lavage fluid are clearly correlated with intratumoral microbiota, and their classification and abundance can be used to assess the severity of non-small cell lung cancer. 253 Proteobacteria is significantly enriched in the broncho alveolar lavage fluid of non-small cell lung cancer, and further subdivision of the bacterial communities is associated with adenocarcinoma and squamous cell carcinoma respectively.…”
Section: The Diagnostic and Prognostic Roles Of Intratumoral Microbiotamentioning
confidence: 99%